RETRACTED: CGVD: a genomic variation database for Chinese populations. Issue Volume 48:Issue D1(2020) (30th October 2019) - Zeng, Jingyao; Yuan, Na; Zhu, Junwei; Pan, Mengyu; Zhang, Hao; Wang, Qi; Shi, Shuo; Du, Zhenglin; Xiao, Jingfa
Abstract: Precision medicine calls upon deeper coverage of population-based sequencing and thorough gene-content and phenotype-based analysis, which lead to a population-associated genomic variation map or database. The Chinese Genomic Variation Database (CGVD; https://bigd.big.ac.cn/cgvd/ ) is such a database that has combined 48.30 million (M) SNVs and 5.77 M small indels, identified from 991 Chinese individuals of the Chinese Academy of Sciences Precision Medicine Initiative Project (CASPMI) and 301 Chinese individuals of the 1000 Genomes Project (1KGP). The CASPMI project includes whole-genome sequencing data (WGS, 25–30×) from ∼1000 healthy individuals of the CASPMI cohort. To facilitate the usage of such variations for pharmacogenomics studies, star-allele frequencies of the drug-related genes in the CASPMI and 1KGP populations are calculated and provided in CGVD. As one of the important database resources in BIG Data Center, CGVD will continue to collect more genomic variations and to curate structural and functional annotations to support population-based healthcare projects and studies in China and worldwide.